1989
DOI: 10.1080/01411598908206865
|View full text |Cite
|
Sign up to set email alerts
|

Pressure effect on phase transition in ferroelectic polymers

Abstract: Pressure effects of phase transition behaviour in two kinds of ferroelectric polymers of poly(viny1idene fluoride), PVDF, and copolymers of vinylidene fluoride and trifluoroethylene, (VDFFrFE), are discussed.In the case of PVDF, several high-pressure treatments including a high-pressure annealing and a uniaxial compression were shown to induce a crystal transformation from a non-polar Form I1 crystal to a polar Form I crystal, which has ferroelectric characteristics and high piezoelectric activity. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 11 publications
2
5
0
Order By: Relevance
“…This means that, when isotropic compression is applied, it is mainly the interchain distance in the a direction that changes (see Figures and ). The conclusion that we deduced from our simulation results is consistent with the experimental result obtained by Matsushige and his co-workers, , in which they studied the role of external pressure and observed enhancement of the β ( I p ) phase under external hydrostatic pressure, and also with the experimental study by Cauda et al, which showed enhancement of ferroelectricity of the β phase after employing the nanoconfinement technique by using a porous alumina membrane. , …”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This means that, when isotropic compression is applied, it is mainly the interchain distance in the a direction that changes (see Figures and ). The conclusion that we deduced from our simulation results is consistent with the experimental result obtained by Matsushige and his co-workers, , in which they studied the role of external pressure and observed enhancement of the β ( I p ) phase under external hydrostatic pressure, and also with the experimental study by Cauda et al, which showed enhancement of ferroelectricity of the β phase after employing the nanoconfinement technique by using a porous alumina membrane. , …”
Section: Resultssupporting
confidence: 92%
“…One interesting feature to note is that, if we compare the variations of the cell parameters in the a and b directions, the change in the a direction is noticeably larger than that in the b direction, even though the magnitudes of the axial stress in the a and b directions along each transition route are all nearly same. This implies that, when the isotropic stress (such as hydrostatic pressure) is applied to the bulk PVDF system, a change of the interchain distance in the a direction should be by far larger than the change of distance in the b direction. , We will have further discussions about this property in relation to the transition behavior from the β ( I a ) phase to the β ( I p ) phase using the AIMD simulation results performed under various simulation conditions in the next section.…”
Section: Resultssupporting
confidence: 80%
“…PVDF normally has a phase transition temperature above the crystal melting point, making direct observation of the ferroelectric-paraelectric phase transition possible only after application of high pressure. 14 More recent studies have identified the paraelectric phase in VDF copolymers as a hexagonal packing of random trans-gauche chains, 12 so that the transition sequence is from paraelectric disordered trans-gauche to the ferroelectric ordered all-trans ␤ structure. Even in this picture, it is possible for an intermediate phase such as ␣ p to appear upon application of an electric field, but there are no reported observations of such an intermediate phase.…”
Section: -6mentioning
confidence: 99%
“…When P͑VDF-TrFE͒ is heated through the ferroelectric-paraelectric phase transition, the alltrans chains develop a disordered trans-gauche conformation packed in a centrosymmetric hexagonal structure and a ͑110͒ lattice spacing that is about 10% larger than that of the ␤ ferroelectric phase. [10][11][12] Application of hydrostatic pressure tends to increase the coercive field 13 and transition temperature 14,15 even to the point of converting the transition type from second order to first order in low-VDF content polymers. 16 It is also possible to convert the paraelectric phase to the ferroelectric phase through the application of an external electric field.…”
Section: Introductionmentioning
confidence: 99%
“…At present, it is understood that at room temperature, it is the α-phase that forms most readily and close to the melting point it is the γ-phase [24][25][26]. The β-phase, which has the largest ferroelectric moment, appears to be the stable phase at higher pressures [27,28], and once obtained it does not normally convert into other phases under ambient conditions. There is an abundance of literature describing the interconversion of one phase into another [24][25][26].…”
Section: Introductionmentioning
confidence: 99%